2018
DOI: 10.1021/acsanm.8b00385
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Resolved Observation of Continuous Interfaces between an As-Grown MoS2 Monolayer and a WS2/MoS2 Heterobilayer on SiO2

Abstract: Van der Waals (vdW) heterostructures synthesized through the chemical vapor deposition (CVD) method allow creation and tuning of intriguing electronic and optical properties of twodimensional (2D) materials. Especially, local structures in the heterostructures, such as interfaces, edges and point defects, are critical for their wide range of potential application. However, up to now atomic scale measurements of local structures in as-grown 2D heterostructures on insulating substrates are still rare. Here we re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(110 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, the stacked region in the HAADF-STEM image (Figure i) exhibits a clear interface between the MoS 2 monolayer and the WS 2 /MoS 2 bilayer, as marked by the yellow dashed line. The MoS 2 monolayer and the stacked region show a perfect hexagonal atomic structure without atomic defects or W atom alloying. , In addition, the intensity profiles of WS 2 and MoS 2 in Figure S11e and S11f clearly display W, S and Mo, S atomic arrangements, respectively, without the incorporation of Mo into WS 2 or the opposite. The atomically clean and sharp interface further confirms the high quality of the as-grown WS 2 /MoS 2 vertical heterostructures.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the stacked region in the HAADF-STEM image (Figure i) exhibits a clear interface between the MoS 2 monolayer and the WS 2 /MoS 2 bilayer, as marked by the yellow dashed line. The MoS 2 monolayer and the stacked region show a perfect hexagonal atomic structure without atomic defects or W atom alloying. , In addition, the intensity profiles of WS 2 and MoS 2 in Figure S11e and S11f clearly display W, S and Mo, S atomic arrangements, respectively, without the incorporation of Mo into WS 2 or the opposite. The atomically clean and sharp interface further confirms the high quality of the as-grown WS 2 /MoS 2 vertical heterostructures.…”
Section: Resultsmentioning
confidence: 95%
“…The scanning tunneling microscopy (STM) measurements were carried out in an ultra-high vacuum (UHV) STM system (Omicron RT-STM). Similar to the previously reported annealing process for 2D MoS 2 [59,60], the sample was annealed at 300 °C for 3 h in the UHV chamber with a base pressure of 4.0 × 10 −10 torr. The STM used a chemically etched tungsten tip.…”
Section: Scanning Tunneling Microscopymentioning
confidence: 99%
“…Heterostructures can be formed by combining different dimensionalities (for instance, 2D/2D, 1D/2D, and zero-dimensional (0D)/2D) or by connecting different phases of the same stoichiometry (e.g., 1T/1H). 1L–2L lateral heterostructures, where the bilayer (2L) is a vertical heterostructure laterally connected to a monolayer (1L), are less common . Scanning tunneling microscopy and spectroscopy (STM/STS) studies of this type of heterostructures revealed the absence of edge states over the continuous transition region from 1L to 2L .…”
Section: Multidimensional Heterostructuresmentioning
confidence: 99%